LA DEUDA EXTERNA PUBLICA PERUANA 1970-2003 - Rospigliosi Ferro, José (2019)
Between 1970 and 2003 the medium and large term Peruvian Public Foreign Debt had receiving of foreign countries an total amount of $ 32 656 million, having amortized $ 31 513 million and having paid as interests a amount of $ 26 549 million, that is meaning a foreign extern service of $ 58 062. This is a minus capitalization of Perú for $ 25 406 millions in this period, that made an annual average of 770 millions that meaning go out more recourses than be income in the country, and this is a falseness of called “extern aid”. The time of greater minus capitalization was between 1986 y 1990.